Lichen as Bioindicator for Monitoring Environmental Status in Western Himalaya, India - Gupta, Sugam; Khare, Roshni; Bajpai, Omesh; Rai, Himanshu; Upreti, Dalip Kumar; Gupta, Rajan Kumar; Sharma, Pradeep Kumar (International Journal of Environment, 2016)
The use of bioindicator communities (lichen) to assess the environmental status of an area is a well-proved strategy to monitor any habitat without any logistic and instrumental facilities. In the present study, 13 bioindicator communities of lichen have been used to assess the environmental status of holy pilgrimage (Badrinath), western Himalaya, India. Three sites (i.e. Badrinath, Mana & pilgrimage route from Bhimpul to Vasudhara) have been comparatively assessed. The results of the study reveals that Badrinath site is less polluted and experiences low degree of anthropogenic disturbances compared to Mana, and pilgrimage route (Bhimpul to Vasudhara). Human settlements, construction of civil works, vehicular emission, and trampling and trekking by tourists are the major threats on these habitats, which ultimately decrease the quality of vegetation and adjacent environment. Controlled vehicular use, promotion of modern way of cooking and managed trekking in these pilgrimage routes could be helpful to combat the decreasing vegetation and environmental quality therein.INTERNATIONAL JOURNAL OF ENVIRONMENTVolume-5, Issue-2, Mar-May 2016 page: 1-15